Leisure program planning and delivery - Russell, Ruth V. 1948-; Jamieson, Lynn Marie 1946- (Human Kinetics, 2008)
Leisure Program Planning and Delivery will guide your students in: employing a comprehensive three-step plan for successful program planning, implementing, and evaluating; learning the essentials of successful recreation programming theory through real-world case studies and examples; and building a professional programming portfolio through completion of class assignments. Leisure Program Planning and Delivery will prepare recreation students for 21st-century programming. The book provides a comprehensive three-step plan for successful programming of services, program leadership, and understanding operational management of program systems in recreation and leisure service organizations. The scope of the book makes it practical either for preparing students and new professionals or for retooling your recreation program for today's challenges. Grounded in contemporary professional practice and real-world applications, the book provides a systematic plan for students to learn the essentials of successful recreation programming, with examples of a variety of activities in community, outdoor, sport, cultural arts, and tourism sectors of the field. Each chapter of Leisure Program Planning and Delivery includes the following student-friendly features: Learning objectives; An opening vignette with a real-world example tied to the theme of the chapter; Photographs, tables, and figures; Examples of specific chapter programming concepts taken from actual programming for outdoor, sport, tourism, cultural arts, and community recreation organizations; A continuing case study highlighting the City of Westerville, Ohio, Parks and Recreation Department, a 2001 and 2007 Gold Medal Awardee; A chapter summary keyed to the learning objectives; A glossary of key terms. Throughout the text, the City of Westerville, Ohio, Parks and Recreation Department--a 2001 and 2007 Gold Medal Awardee--serves as a case study. The case illustrates how program concepts and practices apply in the real world of recreation programming. Leisure Program Planning and Delivery is the foundational text to prepare students and practicing professionals for situations they will encounter on the job. As a reference, the book contains the essentials of programming and offers cutting-edge programming techniques, support tools, and forms that will help professionals meet challenges in leisure programming, making it a text that students will keep long after their course work is completed.